Towards an All-Ireland Diamond Open Access Publishing Platform: the Publish.OA.ie project (Pubmet, 2023)
This talk will present a progress report on the ‘PublishOA.ie’, project in Ireland (2022-24). The objective of PublishOA.ie is to conduct a feasibility study for an All-Ireland digital publishing platform for Diamond Open Access (OA) journals and books, designed to advance best practice and meet the needs of authors, readers, publishers and funders in Irish scholarly publishing.The project is unique in its mandate to report on the feasibility of a shared platform that will be ‘national’ in scope, but encompass academic publishing across two jurisdictions, which are now, post-Brexit, inside and outside the EU: the Republic of Ireland and Northern Ireland in the United Kingdom. The project is led by the Royal Irish Academy (RIA) and Trinity College Dublin (TCD) with 16 partners and affiliates from universities and organisations from the island of Ireland. It is supported by the National Open Research Forum of Ireland (NORF).Publishers and authors of books and journals are collaborating with international and national experts to conduct this feasibility study. First, a research exercise to map Irish academic publishing is being carried out for the first time, and a directory of all publishers in Ireland was published in June 2023.The feasibility study will be based on a review of publishing practices in the island of Ireland, with gap analysis on standards, technology, processes, copyright practices and funding models for Diamond OA, international benchmarking and requirements specification leading to the delivery of a pilot national publishing platform. A set of demonstrator journals and monographs will be published using the platform, which will be actively trialled by the partner publishers and authors.PublishOA.ie is guided by the experience and expertise from members of our international advisory group, including TSV (Finland), Openjournals.nl, DOAJ, SDG Academy, JSTOR, cOAlition S and DIAMAS. Consultation with these international organisations and institutions, all of which have demonstrable and significant experience in the field, are assisting us in analysing and discussing potential solutions to deploy, and where relevant, avail of existing developments. These discussions are proving especially valuable in the context of policy compliance (e.g. cOAlition S), technical advice (e.g. TSV’s use of Public Knowledge Project’s Open Journal Systems), and potential OA content provision.Diverse disciplinary perspectives e.g. from Irish Humanities Alliance, TCD Long Room Hub, Moore Institute (Arts and Humanities) at the University of Galway, Irish Open Access Publishers (IOAP) (multiple disciplines including Social Sciences and STEM), Dublin Institute of Advanced Studies (DIAS) (Physics, Irish language) and the RIA (multiple disciplines including STEM) will be integrated with international best practice. This will inform decisions on models and technical infrastructure tested and trialled ensuring their validity in the Irish context as well as their international validity.Bibliodiversity is at the heart of the PublishOA.ie project, as is long-term sustainability. Publishing in Ireland must always have regard to the considerably larger and better resourced publishing trade in the next-door United Kingdom, where Irish authors, writing as they do in English, have historically had strong representation.PublishOA.ie, aims to increase all-island connections and relationships within and between groups and individuals in scholarly  publishing. The All-Ireland nature of the project strengthens the Shared Island initiative of the Government of Ireland.PublishOA.ie aims to deliver evidence-based understanding of Irish scholarly publishing and of the requirements of publishers to transition in whole or in part to Diamond OA. It will result in increased knowledge of the needs of publishers and authors in Ireland to move towards Diamond OA publishing. Critically, PublishOA.ie will aim to increase awareness and engagement by policymakers of the system-level risks, challenges and opportunities for a publicly owned, centralised platform for Diamond OA publication of journals and books in Ireland.